Comparison of Microstructure and Hardening Ability of DCI with Different Pearlite Contents by Laser Surface Treatment - Zile Wang; Xianmin Zhou; Daxin Zeng; Wei Yang; Jianyong Liu; Qiuyue Shi (Metals, 2025)
Laser surface treatment (LST) has been employed on ductile cast iron (DCI) parts to obtain a good performance and a long service life. There is a need to understand the laser surface-treated microstructure and hardening ability of DCIs with different matrix structures to facilitate the scientific selection of DCI for specific applications. In this study, a Laserline-LDF3000 fiber-coupled semiconductor laser with a rectangular spot was used to harden the surface of ductile cast irons (DCIs) with different pearlite contents. The hardened surface layer having been solid state transformed (SST) and with or without being melted–solidified (MS) was obtained under various process parameters. The microstructure, hardened layer depth, hardness and hardening ability were analyzed and compared as functions of pearlite contents and laser processing parameters. The results show that the MS layers on the DCIs with varied pearlite contents have similar microstructures consisting of fine transformed ledeburite, martensite and residual austenite. The microstructure of the SST layer includes martensite, residual austenite and ferrite, whose contents vary with the pearlite content of DCI. In the pearlite DCI, martensite and residual austenite are found, while in ferrite DCI, there is only a small amount of martensite around the graphite nodule, with a large amount of unaltered ferrite remaining. There exists no significant difference in the hardness of MS layers among DCIs with different pearlite contents. Within the SST layer, the variation in the hardness value in the pearlite DCI is relatively small, but it gradually decreases along the depth in the ferrite DCI. In the transition region between the SST layer and the base metal (BM), there is a steep decrease in hardness in the pearlite DCI, but it decreases gently in the ferrite DCI. The depth of the hardened layer increases slightly with the increase in the pearlite content in the DCI; however, the effective hardened depth and the hardening ability increase significantly. When the pearlite content of DCI increases from 10% to 95%, its hardening ability increases by 1.1 times.